Model Strategi Peningkatan Indeks Desa Membangun (IDM) di Kabupaten Ciamis - Ahmad Zaenudin; Apri Budianto; Aini Kusniawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine and describe the strategy model for increasing the Village Development Index (IDM) in Ciamis Regency, with a focus on environmental resilience, economic resilience, and social resilience. The method used is qualitative descriptive research. The results of the study indicate that the strategy model for increasing IDM in Ciamis Regency still needs improvement in several aspects. In terms of environmental resilience, although there is no pollution, both underdeveloped and developing villages have the potential to be prone to landslides, with developing villages having disaster response efforts, while underdeveloped villages do not. In terms of economic resilience, developing villages show better livelihood diversity compared to underdeveloped villages, although both have sufficient access to trade facilities, but access to financial institutions is limited. In terms of social resilience, although access to education and health is relatively good in both types of villages, the BPJS membership rate is still low, and access to clean water, sanitation, and electricity has reached 100% in developing villages. Access to information and communication already exists, but is not optimal in both villages. This study concludes that increasing IDM requires strengthening environmental, economic, and social resilience that is more integrated and targeted.